Oxford paperback thesaurus - Waite, Maurice (Oxford : Oxford University Press, 2012)
300,000 synonyms and antonyms with thousands of usage examples from real English to show how synonyms are used in context.
Previous ed.: 2006.
Keywords: English language -- Synonyms and antonyms; Thesauri; Electronic books